Total Synthesis of Gelsemiol. Issue 8 (10th January 2013) - Burch, Patrick; Binaghi, Massimo; Scherer, Manuel; Wentzel, Corinna; Bossert, David; Eberhardt, Luc; Neuburger, Markus; Scheiffele, Peter; Gademann, Karl
<x xml:space="preserve">Abstract</x> Let it grow! The neuritogenic iridoid gelsemiol has been prepared in synthetic form by a radical cascade and skeletal rearrangement. This compound accelerates the differentiation of neurons and growth of neuritis (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>